Next generation LoRa-based resilient communication system for disaster mitigation and relief operations - Al-Baraa Ebad; Mohammed Abaker; Bilal A Khawaja; Arshad Karimbu Vallappil; Sameer Qazi; Muhammad Mustaqim (Universitas Ahmad Dahlan, 2026)
This paper presents the development of a long range (LoRa) based communication system meant for off-grid environments. It aims to send data over long distances with minimal power consumption. Using Arduino boards, LoRa transceiver modules, and Bluetooth modules, an analysis of LoRa devices was carried out, focusing on their performance in terms of signal strength and range. LoRa technology is recognized for its low-power consumption and extended range capabilities. The experiments were conducted at the Islamic University of Madinah (IUM), Madinah, Saudi Arabia. The readings of the received signal strength indicator (RSSI) and signal-to-noise ratio (SNR) are collected at various distances. The study involved testing with a 2.15 dBi antenna, and the results indicated that the device achieved a maximum range of 240 m with RSSI = –128 dBm and SNR = –20 dB. This work explored LoRa modulation using software-defined radio (SDR) and demonstrated the feasibility of LoRa technology for off-grid communication. The system offers long-range text messaging capabilities with user-friendly features, serving as a valuable solution where traditional network infrastructure is unavailable.